Changes in hormone levels of participants in a 622-km ultramarathon race based on distance and recovery period - Choi, E. S.; Park, Y.; Ahn, J.; Piao, S.; Lee, Y. H.; Yoon, J. H.; Kwon, M. G.; Shin, K. A.; Kim, Y. J. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Runners who participate in endurance sports such as marathons or ultramarathons have superior physical capabilities and health benefits compared to others. However, they may suffer long-term effects of the negative physiological changes during long-distance running. This study aimed to examine the effects of an ultramarathon on hormone levels, and the associated risks.